The Canonization and Censorship of the Modern Jewish Joke in Alter Druyanow’s Book of Jokes and Witticisms - Sebba-Elran, Tsafi (MiKAN, 2017)
The article discusses Alter Druyanow’s popular work, The Book of Jokes and Witticisms (Sefer Habediha Vehahiddud, 1922) as a turning point in the development of modern Jewish humor. The acceptance of the book is ascribed mainly to its Zionist agenda, expressed not only in the formation of its repertoire but also in the censorship of a large collection of sexual jokes. Following a discussion of Druyanow’s main motives and anthologizing principles, the article presents these jokes for the first time, with the aim of analyzing their social roles. The comparative reading of the jokes in their historical and cultural contexts points to what the Jewish society of that time considered its "other," from competing religious groups to other threatening reference groups within this society, such as women and assimilated Jews. In this way, the censored jokes shed light not only on the marginality of the Eastern European Jews and their feelings of inferiority, but also on their creative response to them, and their ideological horizons.